2021
DOI: 10.3390/jcm10184197
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diagnostic Ureteroscopy Prior to Radical Nephroureterectomy on Oncological Outcomes in Patients with Upper Tract Urothelial Carcinoma: A Comprehensive Systematic Review and Meta-Analysis

Abstract: Background: The incidence of intravesical recurrence (IVR) following radical nephroureterectomy (RNU) is reported in up to 50% of patients with upper tract urothelial carcinoma (UTUC). It was suggested that preoperative diagnostic ureteroscopy (URS) could increase the IVR rate after RNU. However, the available data are often conflicting. Thus, in this systematic review and meta-analysis we sought to synthesize available data for the impact of pre-RNU URS for UTUC on IVR and other oncological outcomes. Material… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
3
33
1
Order By: Relevance
“…The study collectives were too different for this. The application of various techniques, such as the use of a ureteral sheath as protection against recurrence in the urinary bladder, also showed no improvement (35). The extent to which cryobiopsy can circumvent this phenomenon is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…The study collectives were too different for this. The application of various techniques, such as the use of a ureteral sheath as protection against recurrence in the urinary bladder, also showed no improvement (35). The extent to which cryobiopsy can circumvent this phenomenon is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…In a single study included in the present systematic review, patients who underwent URS and delayed RNU had similar CSS and RFS compared to the patients who underwent RNU without previous URS [ 11 ]. Nonetheless, the results of a recent meta-analysis including 16 retrospective series confirmed that URS with biopsy followed by RNU could be associated with significantly worse intravesical RFS (but not with CSS, OS, and metastasis-free-survival), compared to RNU alone [ 16 ]. These findings could be explained by increased risk of tumor seeding during endoscopic biopsy or the manipulation of the ureteroscope.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including meta-analyses, have claimed increased intravesical recurrences after diagnostic URS before RNU [ 2 , 5 , 6 , 7 , 12 , 13 , 14 , 15 ], as is well-known in the urological community. However, although the potential for adverse oncological effects of URS on disease progression has attracted attention and has been hotly debated [ 9 ], cumulative studies have not demonstrated any significant association [ 2 , 5 , 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. However, these studies did not perform detailed subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its diagnostic utility, URS is known to increase intravesical recurrence after RNU [ 2 , 5 , 6 ]. Although previous meta-analyses demonstrated no adverse prognostic impact of URS prior to RNU on survival or progression [ 2 , 7 ], some studies have raised concerns about lymphovascular dissemination of tumor cells via increased intra-ureteropelvic pressure during URS [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%